Since the given complex number is not in the standard form of (a + ib)

Let us convert to standard form,

\( \dfrac{(3 – 2i) (2 + 3i) }{ (1 + 2i) (2 – i)}=\dfrac{6+5i-6(-1)}{2+3i-2(-1)}\)

\(= \dfrac{12+5i}{4+3i}\)

\( \dfrac{12+5i}{4+3i}= \dfrac{12+5i}{4+3i}\times \dfrac{4-3i}{4-3i}\)

\( = \dfrac{63-16i}{25}\)

We know the conjugate of a complex number (a + ib) is (a – ib)

So,

The conjugate of \(\dfrac{ (63 – 16i)}{25}\) is \( \dfrac{ (63 + 16i)}{25}\)

Answered by Aaryan | 1 year agoShow that 1 + i^{10} + i^{20} + i^{30} is a real number?

Solve the quadratic equations by factorization method only 6x^{2} – 17ix – 12 = 0

Solve the quadratic equations by factorization method only x^{2} + (1 – 2i)x – 2i = 0

Solve the quadratic equations by factorization method only x^{2} + 10ix – 21 = 0

Solve the quadratic equations by factorization method only 17x^{2} – 8x + 1 = 0